2008
DOI: 10.1243/09544070jauto516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of ethanol and cetane number improver on the combustion and emission characteristics of a compression ignition engine

Abstract: Combustion and emission characteristics of a direct-injection diesel engine fuelled with diesel—ethanol blends were investigated. The results show that the ignition delay and the premixed combustion duration increase, while the diffusive combustion duration and the total combustion duration decrease with increase in the oxygen mass fraction in the blends. The addition of 0.2 per cent volume fraction of cetane number improver (isoamyl nitrite) could mean that the ignition delay and the premixed combustion durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…More quantity of fuel is burnt in the premixed combustion phase [5,18,20,26,29].It was observed that heat release rate and cylinder gas pressure characteristics were higher for the alumina oxide nanoparticle blended fuels (B20+ 20 NAO, B20+ 30 NAO and B20+ 40 NAO) compared to biodiesel blend B20. This is could be due to accelerated combustion due to the shortened ignition delay, improved atomization, rapid evaporation of fuel, the degree of fuel mixing and uniform burning could have improved [11,26,37,38]. Increase in the ignition delay period had bad effects in fuel atomization and evaporation.…”
Section: International Journal For Research In Applied Science and Engimentioning
confidence: 99%
See 1 more Smart Citation
“…More quantity of fuel is burnt in the premixed combustion phase [5,18,20,26,29].It was observed that heat release rate and cylinder gas pressure characteristics were higher for the alumina oxide nanoparticle blended fuels (B20+ 20 NAO, B20+ 30 NAO and B20+ 40 NAO) compared to biodiesel blend B20. This is could be due to accelerated combustion due to the shortened ignition delay, improved atomization, rapid evaporation of fuel, the degree of fuel mixing and uniform burning could have improved [11,26,37,38]. Increase in the ignition delay period had bad effects in fuel atomization and evaporation.…”
Section: International Journal For Research In Applied Science and Engimentioning
confidence: 99%
“…For different fuels, the values of peak cylinder pressure were increased with the increase of engine load due to the increase of injected fuel mass that results in increasing the amount of heat released. Higher heat release rate and cylinder pressure characteristics were observed for the nanoparticle blended test fuels B20+ 20 NAO, B20+ 30 NAO and B20+ 40 NAO compared to biodiesel blend B20 which was due to the advancement of combustion phase by improved atomization and rapid evaporation of fuel [18,26,39,40]. That cause decreased peak cylinder pressure for blended fuels compared to neat diesel fuel at all engine load range.…”
Section: ) Variation Of Cylinder Peak Pressurementioning
confidence: 99%
“…To overcome this issue, fuel modification is required. Nitrate-based cetane improvers such as triethylene glycol dinitrate (TEGDN), octyl nitrate, isoamyl nitrite were added to ethanol in lower quantities and investigation were carried out with the mixture effect on combustion, performance and emissions of a CI engine at different parameters and geometry by many researchers (Ren et al, 2008;Holland et al, 1992;Simonsen and Chomiak, 1995). Some of researchers reported that there was a drop in power while few have reported the similar results to that of diesel.…”
Section: Introductionmentioning
confidence: 99%
“…Higher cetane numbers reduced the regulated and unregulated emissions including NO x in addition to the improvement in the engine performance [9][10][11]. Several authors [12][13][14] reported that cetane improver in combination with oxygenates improved engine performance in addition to the reduction in emissions. However, these additives are not as effective as EGR for the reduction of NO x emissions.…”
Section: Introductionmentioning
confidence: 99%